A cross-cultural comparison of Ecuadorian and United States face, facework, and conflict styles during interpersonal conflict: An application of face-negotiation theory. Issue 1 (2nd January 2016) - Neuliep, James W.; Johnson, Morgan
ABSTRACT: This study applied and extended face-negotiation theory in a cross-cultural comparison of face, facework, and conflict management styles between Ecuador and the United States (US). Participants included students from the United States and Ecuador. Participants completed a questionnaire that measured face, facework, and conflict style preference in one of two recalled conflict situations that varied in relational closeness (i.e., intimate, nonintimate). Results reveal that Ecuadorian and U.S. students did not differ in their self-face, other-face, and mutual-face concerns. Ecuadorian and U.S. students differed significantly in their preference for facework and conflict style preferences across the two conflict situations, however.